The double-alternative, double-start experimental apparatus: A new procedure for measuring preference - Biederman, G. B. (1984)
A new experimental chamber is described that permits rats to demonstrate behavioral preference for one of two conditions by running towards a goal chamber by one of two routes that are correlated with the different conditions. In a preliminary study, rats chose a route correlated with relatively lower shock, demonstrating the sensitivity of the apparatus. We also report evidence using this device that, of 10 rats tested, all preferred unsignaled rather than signaled, inescapable, unavoidable shock.